Geoquímica das Rochas Máficas Toleíticas da Suíte Pós-Colisional Paulo Lopes, Neoproterozóico do Sul do Brasil - FLORISBAL, LUANA MOREIRA; NARDI, LAURO; BITENCOURT, MARIA DE FÁTIMA; BETIOLLO, LEANDRO MENEZES (Pesquisas em Geociências, 2005)
<!-- .p { text-align: justify; } --> The Paulo Lopes Suite (SPL), composed of the Paulo Lopes Granite (GPL), Garopaba Granitoids (GG) and Silveira Gabbro (GS), is an association of contemporaneous acid and basic rocks, comprising monzo and syenogranites associated to basic dikes, with abundant mafic microgranular enclaves, interpreted as co-mingling products. The contacts between the granitoids and the basic rocks are evidences of coeval and interactive magmas. The Silveira Gabbro occurs in the study area as a main body and several narrow dikes of NNE orientation. Field relations define a chronological order of magmatic events, where the GPL is the first magmatic pulse and, while steel partially crystallized, was intruded by mingled magmas, represented by the GG and the GS. The basic components are medium-grained, equigranular rocks, with subophitic and ophitic textures. The centre of the main body contains medium- to coarse-grained, equigranular rocks, where agglomerates of early-formed clinopyroxene and plagioclase crystals are found. In the chilled margins, they are microporphyritc rocks of aphanitic groundmass, indicative of rapid crystallization. The Silveira Gabbro rocks are composed of labradorite-andesine, orthopyroxene, augite, pigeonite, olivine (occasionally serpentinized), Fe-hornblende and magnesian hornblende, red biotite, magnetite, ilmenite, apatite, and baddeleyite. The composition is tholeiitic, similar to the high-Ti-P basalts of the Serra Geral Formation. Their high contents of K, Rb, Sr and Ba, as well as negative anomalies of Nb and Ta in multielemental diagrams are similar to the ones observed in magmatic rocks from mature arcs or post-collisional environments. The Neoproterozoic basic rocks may be discriminated from the ones belonging to the Cretaceous Serra Geral Formation by their higher contents of alcalis, Cs, U, Th, and by their fractionated REEpatterns, expressed in the La/LuN ratio. The associated granitoids are structural and compositionally compatible with the ones found in post collisional settings, which indicates that the SPL magmatism developed in such environment.